The applicability of family approach tools: self-care promotion, social reintegration and grief experience by an elderly patient (Brazilian Journal of Health Research, 2020)
Introduction: Approaching individuals in their family context is one of the Primary Health Care principles. The Family Health Strategy uses tools deriving from fields such as Sociology and Psychology; among them, one finds genogram, ecomap, life cycles, F.I.R.O, P.R.A.C.T.I.C.E and family conference. These tools are used to intervene in family demands for health services. Objective: Reporting the experience of a primary care team in the application of family approach tools in healthcare provided to an elderly individual. Methods: Qualitative descriptive study of the experience report type. Family approach tools were used as diagnosis and intervention method to assess patient’s family dynamics. Experience Report: A.B., an 81-year-old individual making use of multiple drugs, has sought the Basic Health Unit complaining about pressure in his head. After listening to the patient, health professionals noticed that his symptoms had started after the death of his partner, six years before. It was decided that family approach tools should be used to intervene in the identified issues. Right after analyzing the tools and based on the present case, the following intervention actions were selected: providing instructions about self-care and, mainly, reinforcing the importance of having a social life and of dealing with issues such as grief and family relationship with his children. Conclusion: Family approach tools enabled performing effective interventions focused on improving patient’s condition by not only providing clinical medical care, but also by including the patient in spaces and activities capable of improving his quality of life.
Keywords: Family Health; Family Relationships; Primary Health Care; Interdisciplinary Health Team